2018
DOI: 10.1186/s12885-018-4603-3
|View full text |Cite
|
Sign up to set email alerts
|

Replacing sedentary time with physical activity or sleep: effects on cancer-related cognitive impairment in breast cancer survivors

Abstract: BackgroundEvidence suggests reallocating daily sedentary time to physical activity or sleep confers important health benefits in cancer survivors. Despite emerging research suggesting physical activity as a treatment for cancer-related cognitive impairment (CRCI), little is known about the interactive effects of behaviors across the 24-h period. The present purpose was to examine the cognitive effects of reallocating sedentary time to light-intensity physical activity, moderate-to-vigorous physical activity (M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
24
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 59 publications
1
24
0
1
Order By: Relevance
“…Boyle and colleagues found a significantly lower body mass index and waist circumference when reallocating sleep, sedentary time, or LPA to MVPA . Ehlers et al examined the effect of reallocation of sedentary time on cognitive function, finding reallocation of time to MVPA was significantly associated with better cognitive performance . Collectively, our results and results from previous research demonstrate there are multiple health‐related benefits for breast cancer survivors of replacing sitting time with MVPA and provide evidence for the importance of future research investigating additional objective measures of health outcomes (ie, physical functioning, fitness, and biomarkers) using isotemporal substitution models.…”
Section: Discussionsupporting
confidence: 66%
See 2 more Smart Citations
“…Boyle and colleagues found a significantly lower body mass index and waist circumference when reallocating sleep, sedentary time, or LPA to MVPA . Ehlers et al examined the effect of reallocation of sedentary time on cognitive function, finding reallocation of time to MVPA was significantly associated with better cognitive performance . Collectively, our results and results from previous research demonstrate there are multiple health‐related benefits for breast cancer survivors of replacing sitting time with MVPA and provide evidence for the importance of future research investigating additional objective measures of health outcomes (ie, physical functioning, fitness, and biomarkers) using isotemporal substitution models.…”
Section: Discussionsupporting
confidence: 66%
“…Two other studies have used isotemporal substitution in breast cancer survivors . Boyle and colleagues found a significantly lower body mass index and waist circumference when reallocating sleep, sedentary time, or LPA to MVPA .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These isotemporal results are consistent with findings from previous studies among breast cancer survivors that reported estimated benefits in reallocating time to MVPA. 29,30 In a sample of 256 breast cancer survivors, Boyle et al 30 found a 30-minute reallocation of SB or LIPA to MVPA was associated with lower self-reported waist circumference and BMI. Current lifestyle treatment plans for breast cancer survivors encourage achieving 30 minutes of daily PA and meeting weekly PA guidelines (150 min of MVPA a week) 5 ; however, our findings add to the literature by demonstrating that even an 18-minute shift, or 1 SD, from SB or LIPA to MVPA may have beneficial associations for breast cancer survivors.…”
Section: Discussionmentioning
confidence: 99%
“…Recent isotemporal studies in breast cancer survivor populations suggest it is worthwhile to move beyond examining daily activities independently and start to explore how time spent in activities throughout the day is associated to health. 29,30 The primary aim of this study is to use accelerometer data to construct isotemporal substitution models to assess the associations to cancer recurrence biomarkers of reallocating time spent in SB, LIPA, and MVPA in a sample of postmenopausal breast cancer survivors. The goal of these analyses is to explore how the reallocation of time spent in daytime activities may be beneficial to markers of breast cancer recurrence.…”
mentioning
confidence: 99%